Embryonic Development of Bhakur Catla catla Hamilton 1822 (Cyprinidae) - Tumbahangfe, J.; Subba, Bharat Raj; Jha, S. K. (Our Nature, 2015)
The present study was carried out to investigate the embryonic development of Bhakur, Catla catla. The incubation period of Bhakur was found to be 13 hrs of post fertilization at 30±1oC of water temperature. The present work generated some important information on the early life history and developmental stages of Bhakur in Nepal. This study will help the fishery biologist in understanding the developmental biology of the fish, which might be of great use to take appropriate steps for the sustainable development of the culture, management, and production of indigenous breeds required for fish culture in Nepal climatic condition. DOI: http://dx.doi.org/10.3126/on.v12i1.12257 Our Nature (2014), 12(1):49-53